Work-family trajectories across Europe: differences between social groups and welfare regimes - Firat, Mustafa; Visser, Mark; Kraaykamp, Gerbert (Frontiers in Sociology, 2023)
Introduction Work and family trajectories develop and interact over the life course in complex ways. Previous studies drew a fragmented picture of these trajectories and had limited scope. We provide the most comprehensive study of early-to-midlife work-family trajectories to date. Methods Using retrospective data from waves 3 and 7 of the Survey of Health, Aging and Retirement in Europe (SHARE), we reconstructed work-family trajectories from age 15 to 49 among almost 80,000 individuals born between 1908 and 1967 across 28 countries. We applied multichannel sequence and cluster analysis to identify typical trajectories and multinomial logistic regression models to uncover their social composition. Results The results revealed six common trajectories. The dominant and therefore standard trajectory represents continuous full-time employment with having a partner and children. Women, the lower educated and persons from conservative and liberal welfare regimes are underrepresented in this trajectory, whereas men, higher educated people and those from social-democratic, Eastern European and Baltic welfare regimes are overrepresented. The other trajectories denote a deviation from the standard one, integrating a non-standard form of work with standard family formation or vice versa. Mothers in a stable relationship generally work part-time or not at all. When mostly in full-time employment, women are more likely to be divorced. Lower educated persons are less likely to have work-family trajectories characterized by full-time work and a non-standard family, yet more likely to be non-employed for large parts of their life with standard family formation. Younger cohorts are underrepresented in non-employment trajectories, but overrepresented in part-time employment trajectories along with a partner and children as well as full-time employment trajectories with divorce. Individuals from Southern European and liberal regimes are more likely to be non-working and self-employed partnered parents and those from social-democratic regimes are more likely to be full-time employed divorced parents. We also found pronounced gender differences in how educational level, birth cohort and welfare regime are associated with work-family trajectories from early to midlife. Discussion Our findings highlight the socially stratified nature of earlier-life work-family trajectories in Europe. Potential implications for inequalities in later life are discussed.